Optimasi Protokol Routing ZRP Menggunakan PA-SHORT untuk Mengurangi Jumlah Hop Pada Suatu Rute di Jaringan Manet - Laeli Oktami; Andy Hidayat Jatmika; Nadiyasari Agitha (Journal of Computer Science and Informatics Engineering (J-Cosine), 2019)
The author made modifications to several parts of the ZRP routing protocol, named PASHORT-ZRP. In this study, the authors conducted 5 experiments with which resulted in an increase in throughput on PASHORT-ZRP in the area of ??1000×1000 m2 of 52.081 % for node 20, 81.475 % for nodes 60, and 34,912 % for node 100. Results of average end-to-end delay in PASHORT-ZRP contains a decrease of 0.737 % for node 20, 0.365 % for node 60, and 0.939 % for node 100 in area 500×500 m2. The results of the packet delivery ratio on PASHOR-ZRP found an increase of 64.931% for node 20, 7.763% for node 60, and 26.644% for node 100 in the area of ??500×500 m2. in the 1000×1000 m2 area the results of routing overhead on PASHORT-ZRP contain a decrease of 36,815 % for node 20, 56.267 % for node 60, and 37.538 % for node 100.